The Contribution of AI to the Development of Teaching - Ge, Shan (Transactions on Economics, Business and Management Research, 2024)
The rapid development of artificial intelligence (AI) has made excellent contributions to the development of teaching This contribution is reflected not only in the breakthrough of the traditional teaching methods, but also in targeted solutions to the differences in the individual learning situation of students, which can effectively improve students’ academic performance. Thus, AI is very important in education. This paper starts from the mainstream function of AI, focuses on the application of it in teaching, and makes exploration of the future of teaching.